2018
DOI: 10.1021/acs.jctc.7b01093
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Diffusion Coefficients through Coarse-Grained Simulations Using the Automated-Fragmentation-Parametrization Method and the Recovery of Wilke–Chang Statistical Correlation

Abstract: We introduce a model for the calculation of diffusion coefficients using dissipative particle dynamics coarse-grained molecular simulations. We validate the model on experimental diffusion data of small organics and drug-like molecules in water. The new model relies on our automated-fragmentation-parametrization protocol for cutting molecules into fragments, which are calibrated using the COSMO-RS thermodynamic model (10.1021/acs.jcim.6b0000327806564J. Chem. Inf. Model.20165623612377). By simulations over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…For partially soluble pairs where reliable solubility data are not available, the predictive method such as COSMOtherm can be used to obtain the corresponding iDACs. Different top-down approaches to obtain DPD parameters using COSMOtherm are introduced recently. Conceptually, the surface charge density distribution of a molecule is first determined using quantum chemical calculations using the Turbomole program at the COSMO-BP-TZVP optimized basis set. ,, The obtained charge-density probability distributions are then used to predict the thermodynamic properties between molecules based on a conductor-like solvation model for real solvent (COSMO-RS) theory. Here, the iDACs of the reference molecules (in Table ) for acid–tail and head–tail pairs are obtained by BIOVIA COSMOtherm software followed by a rescaling based on eq . ln­(γ TW ∞ ) is the average value of the logarithmic iDACs for hexane and water, and ln­(γ TW ∞ ) is that for carboxyl acid and hexane.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For partially soluble pairs where reliable solubility data are not available, the predictive method such as COSMOtherm can be used to obtain the corresponding iDACs. Different top-down approaches to obtain DPD parameters using COSMOtherm are introduced recently. Conceptually, the surface charge density distribution of a molecule is first determined using quantum chemical calculations using the Turbomole program at the COSMO-BP-TZVP optimized basis set. ,, The obtained charge-density probability distributions are then used to predict the thermodynamic properties between molecules based on a conductor-like solvation model for real solvent (COSMO-RS) theory. Here, the iDACs of the reference molecules (in Table ) for acid–tail and head–tail pairs are obtained by BIOVIA COSMOtherm software followed by a rescaling based on eq . ln­(γ TW ∞ ) is the average value of the logarithmic iDACs for hexane and water, and ln­(γ TW ∞ ) is that for carboxyl acid and hexane.…”
Section: Methodsmentioning
confidence: 99%
“…Groot and Warren linked the parameters to the Flory–Huggins parameters, making DPD suitable for modeling polymeric systems . Recent advances in parameterization include finer coarse-grained-based algorithms to improve the accuracy of the model, ,, and the linking to the quantum-chemical-based method such as COSMOtherm for handling the interactions between uncommon chemical fragments. It is suggested that the nonbonded interaction parameters should be determined concurrently with the bonded parameters. , One approach is to obtain the bonded parameters by reproducing the molecular configurations of the chain molecules from MD simulations and to obtain nonbonded parameters by linking to infinite dilution activity coefficients (iDAC) obtained by COSMOtherm or experimental data. The method has been proven applicable to modeling self-assembly of amphiphiles, including surfactants and polymer electrolytes. …”
Section: Introductionmentioning
confidence: 99%
“…To quantitatively describe the morphologies of GO sheets, the radius of gyration tensor S , the relative shape anisotropy, and the solvent accessible surface area (SASA) are calculated (Supporting Information). The hydrodynamic radius, R h , is computed via Stokes–Einstein relations, with the translational and rotational diffusion coefficients, D t and D r , which are calculated by the mean-square displacement (MSD) and angular mean-square displacement (AMSD), respectively. , …”
Section: Simulation Methodsmentioning
confidence: 99%
“…In previous publications, we have discussed automated coarse-graining protocols to calculate partition coefficients 1 and diffusion coefficients. 2 In this work, we focus on providing a fast and reliable method for calculating the alkane/water partition coefficient of lead-like molecules with a molecular weight of up to 800. As far as modeling is concerned, predicting large-molecule partitioning in a practical industrial setting is extraordinarily difficult.…”
Section: Introductionmentioning
confidence: 99%